STUDI KOMPARASI KAPASITAS DUKUNG RENCANA DAN KAPASITAS DUKUNG AKTUAL FONDASI TIANG PANCANG PADA KONSTRUKSI SLAB ON PILE JALAN TOL SEMARANG – DEMAK SEKSI 2 - Agung Hari Wibowo; Sulardjaka Sulardjaka; Silviana Silviana (Jurnal Teknik Indonesia, 2024)
Semarang - Demak Toll Road Section 2 with a length of 16.31 km crosses the North Coast of Java. The regional geological map shows that the North Coast of Java has alluvial soil layers with clay and silt characteristics. The results of soil investigations show that the depth of the soft layer reaches more than 60 m. This condition triggers construction engineering to support the Highway above it. One of the efforts to fulfill the elevation plan (finish grade) is the flyover concept with slab on pile construction. The planned traffic lane is laid on a concrete slab which is supported by piles with a diameter of 600 mm. With sufficiently deep soft soil layers, the bearing capacity of the foundation piles is borne by the frictional resistance provided by the soil along the piles. This comparative study compares the planned carrying capacity calculated by the empirical formula with the actual carrying capacity of the field as a result of the PDA Test. Calculations were made on 5 test poles for later comparisons were made with the PDA test record data. For the case of 14 days driving at the research location, the pile bearing capacity from the PDA test results is still below the design bearing capacity. The average actual carrying capacity obtained from the 5 test piles is 278 tons. This value is below the planned carrying capacity of the Shio & Fukui method of 381 tons, Meyerhoff's 355 tons, Biaud et al's 777 tons, and Luciano Decourt's 605 tons. At the age of the pile 14 days after the erection was completed, the results of the calculation of the bearing capacity of the Meyerhoff method are closest to the actual bearing capacity of the PDA test results with a ratio of 1.26. The next method is Shio & Fukui with a ratio of 1.36, Luciano Decourt (2.16), and Biaud et al (2.81). Some of the results of previous studies showed a positive correlation between the age after completion of the pile and the frictional carrying capacity. For this type of friction pile, this is of course very influential, so that it is possible that when it is realized that it is carried out with a longer service life, the actual bearing capacity obtained will increase. This requires further research to obtain a time relationship with an increase in pile bearing capacity, especially for locations that have deep soft soil layers such as in this study location.